Trigger behaviour and shooting performance in elite biathletes: effects of physical load and shooting positions - Wiesinger, H.-P.; Birklbauer, J.; Buchecker, M.; Dirnberger, J.; Sattlecker, G. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: In biathlon athletes and coaches, there is a consensus that poor trigger control increases rifle motion, making it more challenging to hit the target. However, experimental evidence on the relationship between trigger behaviour and rifle motion or shooting performance remains inconclusive 1,2 . Previous studies using mean values for each biathlete and variable may have produced misleading results due to inter-individual differences 3. Here, we use a statistical approach that includes each shot to account for intra-individual differences to provide a more nuanced and practical interpretation of trigger behaviour`s impact on performance.